Enterobacter-inoculation altered the C, N contents and regulated biomass allocation in Reaumuria soongorica to promote plant growth and improve salt stress tolerance - Bao, Xin-Guang; Chong, Pei-Fang; He, Cai; Lu, Xue-Mei; Wang, Xue-Ying; Zhang, Feng; Tan, Bing-Bing; Yang, Jia-Li; Gao, Li-Li (Frontiers in Plant Science, 2025)
Soil salinization poses a significant ecological and environmental challenge both in China and across the globe. Plant growth-promoting rhizobacteria (PGPR) enhance plants’ resilience against biotic and abiotic stresses, thereby playing a vital role in soil improvement and vegetation restoration efforts. PGPR assist plants in thriving under salt stress by modifying plant physiology, enhancing nutrient absorption, and synthesizing plant hormones. However, the mechanisms through which PGPR regulate the contents of carbon (C) and nitrogen (N), and biomass allocation of desert plant in response to salt stress is still unclear. This study explores the impact of PGPR on biomass allocation, C, and N contents of R. soongorica seedlings through a pot experiment. Strains P6, N20, and N21, identified as Enterobacter, were isolated from the rhizosphere of R. soongorica, and they exhibited various beneficial traits such as indole-3-acetic acid (IAA) production, phosphate solubilization, nitrogen fixation, and tolerance to up to 8% NaCl stress. We found that under NaCl stress, R. soongorica seedlings exhibit significant reductions in plant height, basal diameter, and root surface area (P<0.05). However, inoculation with strains P6, N20, and N21 reverses these trends. Compared to NaCl treatment alone, co-treatment with these strains significantly increases the biomass of roots, stems, and leaves, particularly root biomass, which increases by 99.88%, 85.55%, and 141.76%, respectively (P<0.05). Moreover, N contents decrease significantly in the roots, stems and leaves, C contents increase significantly in the roots and leaves compared to NaCl treatment (P<0.05). Specifically, N contents in roots decrease by 14.50%, 12.47%, and 8.60%, while C contents in leaves increase by 4.96%, 4.45%, and 4.94%, respectively (P<0.05). Additionally, stem and leaf biomasses exhibit a significant positive correlation with C contents and a significant negative correlation with N contents in these tissues. In conclusion, inoculation of Enterobacter strains enhanced the biomass of R. soongorica seedlings, regulated the biomass distribution, and modifies C and N contents to promote plant growth and improve salt stress tolerance. This study provides a novel adaptive strategy for the integrated use of PGPR and halophytes in saline-alkali soil improvement and vegetation restoration efforts.